Climate Change Impact on Environmental Variability in the Forest - Nunes, Leonel (2021)
This book discusses the impact of climate change on rural forest areas. It analyses data provided by the Portuguese Institute of the Sea and Atmosphere (IPMA) to not only demonstrate that climate change has occurred in Portuguese forests, but also to suggest how forestry practices can be adapted to minimise its effects. In turn, the book distils data collected over several years into a comprehensive and coherent review of the ways in which the climate has changed in Portugal. It addresses the changes in rainfall, temperatures, and climatic anomalies, and how these changes correlate with effects such as rural forest fires. Though the text chiefly focuses on Portugal, the tools implemented are easily transferable to other countries and regions, making it relevant to readers around the globe. The book offers a valuable asset for students, researchers, foresters and those working at environmental (research) institutions.